A dataset of interprovincial food trade flows in China - Lan Luo; Zhencheng Xing; Yifan Liu; Xiang Liu; Lingling Jiang; Yi Peng; Haibo Zhang; Haikun Wang (Scientific Data)
Abstract Understanding the food trading network is crucial for optimizing resource allocation, maintaining stability in the food system, and safeguarding food security. However, as one of the world’s largest agricultural producers, there is a dearth of publicly available data sources pertaining to China’s interprovincial physical food trade. Here, we developed a dataset of interprovincial physical food flows in Chinese mainland for the period 2000–2022, using the trade gravity model with the integration of food supply, food demand, and transportation data. This dataset includes 15 key types of plant-based and animal-based food products and represents the longest time series covering the most extensive variety of food products to date on China’s food trade patterns. The dataset reveals changes in dietary structures and trade patterns across regions within China since the 21st century. This work provides a methodological framework and dataset that could support studies on virtual resources flow, agri-environmental impact assessment, and food policy formulation across various food categories and regions.